Anthropology of perfection in traditional cosmology - Zekrgoo, Amir Hossein (s.n, 2012)
The present study is aimed at identifying the attributes of perfection in traditional doctrines. It will address the archetypal qualities by which certain individuals throughout the history of East and West-also within the worldviews of ancient myths, spiritual orders and official religions were regarded as heroes, sages, saints or prophets. In the same line the terminologies related to human perfection in various faiths - such as Ibn Arabi's "Perfect man" (al-Insan al-kamil) or "Exalted Man" (al-Insan al-Arfa) Hindu's Jivan-mukta, Buddhist's Chakravartin etc. Will be introduced the scope of the study will also extend to modern conception of perfection as manifested in the imaginative attributes of the superhero characters